Within-host dynamics shape antibiotic resistance in commensal bacteria - Davies, Nicholas G. (Nat Ecol Evol, 2019)
The spread of antibiotic resistance, a major threat to human health, is poorly understood. Simple population-level models of disease transmission predict that above a certain rate of antibiotic consumption in a population, resistant bacteria should completely eliminate non-resistant strains, while below this threshold they should be unable to persist at all. This prediction stands at odds with empirical evidence showing that resistant and non-resistant strains coexist stably over a wide range of antibiotic consumption rates. Not knowing what drives this long-term coexistence is a barrier to developing evidence-based strategies for managing the spread of resistance. Here, we argue that competition between resistant and sensitive pathogens within individual hosts gives resistant pathogens a relative fitness benefit when they are rare, promoting coexistence between strains at the population level. To test this hypothesis, we embed mechanistically-explicit within-host dynamics in a structurally-neutral disease transmission model. Doing so allows us to reproduce patterns of resistance observed in the opportunistic pathogens Escherichia coli and Streptococcus pneumoniae across European countries, and to identify factors that may shape resistance evolution in bacteria by modulating the intensity and outcomes of within-host competition.